The effect of diabetes mellitus on oral health-related quality of life: A systematic review and meta-analysis study - Yousef Mohseni Homagarani; Kimia Adlparvar; Saba Teimuri; Mohammad Javad Tarrahi; Firoozeh Nilchian (Frontiers Media S.A., 2023)
BackgroundDiabetes mellitus is related to variable dental and oral complications like xerostomia and periodontal problems. Therefore, diabetes can affect the oral status and oral health-related quality of life (OHRQoL). A systematic review of evidence can determine the association between diabetes and OHRQoL. so, this study aimed to evaluate the effects of diabetes on OHRQoL.MethodsAfter determining the PECO and eligible criteria, a comprehensive search was conducted in PubMed, Scopus, Web of Science, and Embase without any restriction. Further searches were performed in Google Scholar and reference lists of selected articles. Two independent reviewers carried out paper selection, data extraction, and quality assessment. A meta-analysis was conducted using a "random effect model" and the standardized mean difference of OHRQoL with a 95% confidence interval (CI) was reported as estimating pooled effect size.ResultsAfter screening 237 identified records, three case-control and ten cross-sectional studies met eligibility criteria. Two cross-sectional studies were excluded in the quality assessment phase and the rest of the studies have a low or moderate risk of bias. The pooled standardized mean difference between the case and the control groups was 0.148 (95% CI: −0.045 to 0.340).ConclusionDiabetes mellitus has no statistical significant association with OHRQoL. Nevertheless, based on the articles' review, it seems that diabetes can lead to functional limitations, physical pain, and psychological discomfort. Also, complications of diabetes adversely affect wellbeing. Hence dentists can play an essential role in the awareness of persons with diabetes about these problems and improve their OHRQoL.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022303038, identifier CRD42022303038.